Effectiveness of Nutritional Counseling on Improving Dietary Compliance Among Pregnant Women - khusnul khotimah; Nofilia Sacharum (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Maternal nutrition during pregnancy is critical in supporting maternal health and fetal development. However, many pregnant women do not adhere to recommended dietary practices, which may increase the risk of complications. Nutrition counseling has been proposed to improve compliance with healthy dietary behaviors. Objectives: This study aimed to evaluate the effectiveness of nutrition counseling on improving dietary compliance among pregnant women. Methods: A quasi-experimental design with a non-equivalent pretest–posttest control group was employed. Forty pregnant women in their second and third trimesters were recruited and assigned to two groups: an intervention group receiving structured nutrition counseling and a control group receiving routine antenatal care. Dietary compliance was assessed using a validated questionnaire before and after a four-week intervention. Data were analyzed using paired t-tests for within-group comparisons and independent t-tests for between-group differences. Results: The intervention group showed a significant improvement in dietary compliance scores after counseling (mean increase 0.85, p < 0.005), whereas the control group demonstrated no significant change (mean increase 0.15, p = 0.120). Post-intervention comparisons indicated a significantly higher compliance score in the intervention group compared to the control group (p < 0.001; α<0.05). Conclusions: Nutrition counseling was effective in enhancing dietary compliance among pregnant women. Integrating structured counseling into antenatal care has the potential to foster healthier eating behaviors, reduce pregnancy-related complications, and improve maternal and fetal outcomes. Further research is needed to examine long-term effects and its scalability in different healthcare settings.